APOE alleles are not associated with calcific aortic stenosis. Issue 10 (10th April 2006) - Ortlepp, J R; Pillich, M; Mevissen, V; Krantz, C; Kimmel, M; Autschbach, R; Langebartels, G; Erdmann, J; Hoffmann, R; Zerres, K
Abstract : Objectives: To analyse the association of APOE alleles with aortic stenosis (AS) in a large study population. Methods: Patients with AS (n  =  538) and a control group of the same age without heart disease (n  =  536) were recruited. Left heart catheterisation was performed and mean gradient, aortic valve area, presence of stenotic coronary artery disease (CAD) and cardiovascular risk factors (hypercholesterolaemia, hypertension, smoking, diabetes mellitus and family history of CAD) were assessed. The frequency of the APOE major alleles e2, e3 and e4 was assessed by genotyping the polymorphisms APOE334 and APOE472 with a 5′ exonuclease assay (TaqMan). Results: Mean gradient across the aortic valve in cases was 50 (SD 20) mm Hg corresponding to a mean aortic valve area of 0.84 (SD 0.34) cm 2 . 270 patients with AS had stenotic CAD. Among patients with AS, the prevalence of hypercholesterolaemia (64% v 40%, p < 0.001), smoking (43% v 27%, p < 0.001), diabetes (27% v 17%, p < 0.01), family history of CAD (30% v 21%, p ⩽ 0.05), and male sex (65% v 44%, p < 0.001) was higher in those with than in those without CAD. The frequency of the major alleles was not different between cases and controls (APOE e2: 104 (19.3%) v 94 (17.5%); APOE e3: 319 (59.3%) v 332 (61.9%); APOE e4: 115 (21.3%) v 110 (20.5%); all p > 0.10). Conclusion: APOE e4 is not associated with AS, reflecting the different genetic backgrounds of CAD and AS.